TOPICAL TEACHERS’ WORK TECHNIQUES IN EDUCATION PROCESS OF PUPILS WITH MENTAL DISORDERS - Rozenfelde, Marite (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The paper describes the study on efficient and less effective teachers' work techniques in lessons, working with pupils with mental disorders and implementing the inclusive educational process that is governed by Latvian national and educational policies. The summary of the answers of comprehensive and special schools' teachers involved in research also indicates a number of additional factors that are significant in the learning process of pupils with mental disorders and can contribute to or reduce pupils' learning achievements.